Fetus in fetu: Case report - Carmona-Meza, Zenen (2016)
Fetus in fetu is a rare condition, which has fewer than 200 cases reported to date. It is mainly located in the retro peritoneum; but it can occur at other levels. Treatment is always surgical and early detection and extraction allows clinical improvement and the successful development of the affected child. We report the case of an 18 month infant who is carried by her mother to medical appointment due to low weight for that age. In the physical exam, doctor found mass in the left hypochondrium and epigastrium and a total abdominal ultrasound is requested. Ultrasound reports findings relating to right hydronephrosis, and excretory urography and a CT with contrast reveals fetus parasite located in retro peritoneum. The infant is taken to surgery for lysis of peritoneal adhesions, resection of retroperitoneal tumor, and ureterolysis nephropexy. After this, the infant presented good evolution. Early detection of these cases is necessary to allow a good development of the child; but this begins from a good medical care, that allows its identification and treatment.